70 kV computed tomography of the thorax: valence for computer-assisted nodule evaluation and radiation dose – first clinical results. (November 2014) - Bodelle, Boris; Klement, Dorothée; Kerl, Josef Matthias; Lehnert, Thomas; Frellesen, Claudia; Bauer, Ralf; Vogl, Thomas Josef; Sedlmair, Martin; Schulz, Boris
Background: Computed tomography (CT) is the gold standard for evaluation of pulmonary nodules and is at the same time responsible for the majority of the collective effective dose. Purpose: To evaluate radiation dose and efficacy of computer-assisted detection (CAD) for solid pulmonary nodules in low dose chest CT performed at 70 kV. Material and Methods: CAD was performed upon chest CT with 70 kV and 100 kV (gold standard) at manufacture's recommended tube current of 87 mAs (collimation, 64 × 0.6 mm). Detection rate for pulmonary nodules and size measurements of both techniques were compared to each other. Radiation dosage in terms of effective dose (E) was measured using an Alderson-Rando Phantom. Results: Seventy-four patients with 301 solid nodules were included in the study. CAD detection rate was similar for 70 kV (94.7%) and 100 kV (92.4%). Mean transversal nodule diameter was 5.5 mm for 70 kV and 5.7 mm for 100 kV with an average volume of 0.12 mL (both techniques). Derived from the phantom measurements patient examinations resulted in an E of 0.51 mSv (70 kV) versus 2.02 mSv (100 kV). Conclusion: 70 kV low-dose chest CT is suitable for CAD based lung nodule analysis at a fraction of the radiation burden of the standard technique. Since the measurements are highly accurate, 70 kV CT could be used for detection of pulmonal lesions as well as follow-up studies.